Magnetohydrodynamic time-dependent computational natural convection flow, heat and mass transfer in inclined semi-circular enclosures. Issue 8 (7th November 2016) - Rahman, M.M.; Öztop, Hakan F.; Saidur, R.; Naim, A.G.; Al-Salem, Khaled S.; Ibrahim, Talaat A.
Abstract : Purpose: The purpose of this paper is to make a numerical analysis on unsteady analysis of natural convection heat and mass transfer to obtain flow field, temperature distribution, and concentration distribution. Design/methodology/approach: A finite element method is applied to solve governing equations of natural convection in curvilinear-shaped system for different parameters as thermal Rayleigh numbers (103=RaT =106), inclination angle (0°=φ=60°) and Hartmann numbers (0=Ha=100). Findings: Both magnetic field and inclination angle can be used as control parameter on heat and mass transfer. Flow strength decreases almost 100 percent between Ha =0 and Ha =100 on behalf of the higher values of thermal Rayleigh number. Originality/value: The originality of this work is to application of magnetic field on time-dependent natural convection flow, heat and mass transfer for curvilinear geometry.